(untitled) (Revista Contexto & Educação, 2024)
Blended learning proposes the convergence of pedagogical practices in face-to-face and online education. The objective of investigating how the learning trajectories of the teachers’ digital teaching are configured and to analyze teachers ‘perception of teacher training for use technology. A qualitative approach and methodological strategy of the case study type used the exploratory questionnaire and narrative interviews. The triangulation of the produced data was explained by Narrative Analysis, with the aid of the NVIVO tool. The research scenario is the Instituto Federal Farroupilha and the research subjects are the teachers who work in this institution. An analysis of the data evidenced that most teachers are unaware of blended learning but are interested in trying new ways of teaching and learning through TIC, since they have been insufficiently addressed in teacher training. It was concluded that hybrid teacher training is a viable way to promote the learning of digital teaching.